Design, Synthesis, and Apoptosis-Promoting Effect Evaluation of Rhopaladins’ Analog 4-Arylidene-5-Oxopyrrolidine Derivatives - Zhu, Jun; Kong, Ling-Qi; Chen, Qin-Hua; Li, Bin; Wu, Lun; Ran, Feng-Ying; Ke, Li-Na; Zeng, Xiao-Hua; Wang, Hong-Mei (Frontiers in Chemistry, 2022)
Marine alkaloids have novel structures and antitumor activities. Therefore, we synthesized rhopaladins’ analogs from marine alkaloids rhopaladins A-D and modified their structures to synthesize 4-benzylidene-5-pyrrolidone derivatives. Among the compounds, (2E, 4E)-4-(4-chlorobenzylidene)-2-(4-chlorostyryl)-N-cyclohexyl-1-(4-fluorophenyl)-5-oxopyrrolidine-2-carboxamide (RPDPRH) has high efficiency and less hepatotoxicity, with IC50 values of 4.66, 6.42, 17.66, 15.2, 12.36, 22.4, and 243.2 μM in vitro anti-proliferative activity testing against cervical cancer C-33A, CaSki, SiHa, and HeLa cells, human hepatocarcinoma HepG2 and 7402 cells, and human normal liver LO2 cells, respectively. In particular, RPDPRH has similar activity to cisplatin on human hepatocarcinoma cells, and cisplatin served as a positive control in our study. Next, the apoptosis of HepG2 and 7402 cells induced by RPDPRH at different concentrations was detected by Annexin V/PI flow cytometry. Moreover, the expression of apoptotic proteins was detected by Western blot analysis. Finally, the results showed that RPDPRH could induce apoptosis of hepatocarcinoma cells by regulating Bax and Bcl-2 expressions. In summary, our results indicate that RPDPRH has the potential to serve as an antitumor agent and plays a significant role in future studies.